Perbandingan kualitas hubungan Leader - member exchange terhadap Followers Outcome pada perkembangan digital startup - Tuzzahra, Zabrina; ER, Mahendrawati (Komputika : Jurnal Sistem Komputer, 2025)
The quality of relationships between employees in a growing company greatly influences increasing followers outcomes, this is also inseparable from the role of a leader or team leader. The leader-member exchange (LMX) theory is a leadership theory that considers the dyadic relationship between leaders and team members, where each relationship quality certainly has different follower outcomes. The purpose of this study was to analyze the differences in the quality of relationships that occur between team leaders and team members during organizational change in each phase. The data used in the study were obtained from a digital startup company in East Java, in 3 different divisions in each phase and processed using the case study research method. The results of the study prove that there are differences in the quality of relationships in the first phase, the quality of the relationship is classified as negative, while in the second phase it is positive. And an anomalous phenomenon was found in the quality of the relationships analyzed.